Changes in human fetal oxygenation during maternal hyperoxia as estimated by BOLD MRI. (12th December 2012) - Sørensen, Anne; Peters, David; Simonsen, Carsten; Pedersen, Michael; Stausbøl‐Grøn, Brian; Christiansen, Ole Bjarne; Lingman, Göran; Uldbjerg, Niels
ABSTRACT Objective Changes in blood oxygen level dependent (BOLD) magnetic resonance imaging (MRI) signal are closely related to changes in fetal oxygenation. In this study, we aimed to investigate the changes in human fetal oxygenation during maternal hyperoxia by using the non‐invasive BOLD MRI technique. Method Eight healthy pregnant women in gestational week 28 to 34 were included. With the use of a facial oxygen mask, we induced maternal hyperoxia and measured changes in the BOLD MRI signal of selected fetal organs. Results In a number of fetal organs, the BOLD MRI signal increased significantly (P < 0.01) during maternal hyperoxia (mean change in % ± SEM): liver (14.3 ± 3.7%), spleen (15.2 ± 3.5%) and kidney (6.2 ± 1.8%) as well as the placenta (6.5 ± 1.6%). In the fetal brain, however, the BOLD MRI signal remained constant (0.3 ± 0.2%). Conclusion During maternal hyperoxia, we demonstrated an increased oxygenation in a number of human fetal organs by using the non‐invasive BOLD technique. The oxygenation of the fetal brain remained constant, thus a 'reversed' brain sparing mechanism could be considered in healthy fetuses subjected to hyperoxia. © 2012 John Wiley & Sons, Ltd.